2018
DOI: 10.1186/s40677-018-0099-z
|View full text |Cite
|
Sign up to set email alerts
|

A rationale for effective post-fire debris flow mitigation within forested terrain

Abstract: Watersheds recently burned by wildfires are recognized as having an increased susceptibility to debris flow occurrence. The great majority occur within the first 2 years following wildfires. These debris flows are generated primarily through the process of progressive entrainment of material eroded from hillslopes and channels by surface runoff and appears independent of the vegetative community burned. The decreased likelihood of debris flows over time is linked to the restoration of hydrologic function as ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Many difficulties need to be addressed in an attempt to assess landslide risk in burnt areas; they are even higher in densely populated neighborhoods, where the presence of man and his activities can be at the origin of fires (they are, in fact, one of the main operations used by man to remove vegetation along the slopes in an attempt to claim new land for pasture or construction purposes). As evidenced in the scientific literature, wildfires seem to act as a predisposing factor, which is then triggered by rainfall [27][28][29]. The latter consideration has been confirmed in a similar geological context concerning the Campania region (Sarno Mountains) by [30] and for the study area by [31].…”
Section: Introductionsupporting
confidence: 62%
“…Many difficulties need to be addressed in an attempt to assess landslide risk in burnt areas; they are even higher in densely populated neighborhoods, where the presence of man and his activities can be at the origin of fires (they are, in fact, one of the main operations used by man to remove vegetation along the slopes in an attempt to claim new land for pasture or construction purposes). As evidenced in the scientific literature, wildfires seem to act as a predisposing factor, which is then triggered by rainfall [27][28][29]. The latter consideration has been confirmed in a similar geological context concerning the Campania region (Sarno Mountains) by [30] and for the study area by [31].…”
Section: Introductionsupporting
confidence: 62%
“…Several additional authors have observed landslides in areas that burned 5 or more years beforehand (Benda and Dunne 1997;May and Gresswell 2003;Meyer et al 2001;Rice and Foggin 1971). These landslides can subsequently transition into debris flows (De Graff 2018;Jackson and Roering 2009;Woodsmith et al 2004Woodsmith et al , 2007. The increase in landslide susceptibility after wildfire has been attributed to increases in soil moisture that persists for several years after wildfire as a result of decreased evapotranspiration (Helvey 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in landslide susceptibility after wildfire has been attributed to increases in soil moisture that persists for several years after wildfire as a result of decreased evapotranspiration (Helvey 1980). In addition, researchers have found that roots can lose strength following fire, thereby reducing the apparent cohesion provided by roots and leaving hillslopes more prone to failure (De Graff 2018;Gehring et al 2019;Jackson and Roering 2009;Lanini et al 2009;Regelbrugge and Conard 1993). Modeling studies have shown that post-fire landslides are an important contributor of sediment to low-order channels (Martin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The sediment cascade conceptual model creates a useful framework to explore and describe wildfire‐induced changes. The sediment cascade is composed of geomorphic process domains (Wohl, 2010) that operate at different spatial scales [e.g., rainsplash (Gabet & Dunne, 2003; Moss, 1988; Moss et al., 1979) at 1 × 10 −1 m to debris flows (Kean, Staley, et al., 2019; Prochaska, Santi, Higgins, & Cannon, 2008) at 1 × 10 6 m] and temporal scales [e.g., nearly instantaneous dry‐ravel during fire (DiBiase & Lamb, 2013) to landslides years to decades after wildfire (De Graff, 2018; Jackson & Roering, 2009; Rengers et al., 2020)].…”
Section: Introductionmentioning
confidence: 99%